The Psycho-Social Effects of Integrating Former Armed Militias in Organized Security Architecture: the Nigerian Model - Da-Cocodia, Al-Bashir T. Olalekan; Oloje, Edward Adeshina (Journal of Contemporary International Relations and Diplomacy, 2026)
This paper interrogates psycho-social effects of integrating former armed militias into Nigeria’s organized security architectures and governed spaces. It is theoretically anchored on Post-Conflict Reintegration Theory which provides a foundational lens for understanding the transformation of former militia members as they transition from armed violence into formal state security structures by illuminating the institutional and psychosocial processes required to transition ex-combatants from insurgency to legitimate security actors- emphasizing the importance of trust-building, inclusion, and normative adaptation. Using a qualitative analytical approach grounded in secondary data, the study finds that while integration enhances operational capacity and community-level intelligence, it simultaneously reproduces identity dissonance, institutional mistrust, and security fragmentation. The findings underscores that sustainable reintegration must balance identity transformation, psychosocial stability, and state legitimacy. It concludes that Nigeria’s security reform must shift from reactive securitization to inclusive reintegration models that humanize ex-combatants while reinforcing democratic governance and public trust.